Rare allele enrichment and detection by allele-specific PCR, competitive probe blocking and melting analysis - Luming Zhou; Ying Wang; Carl T. Wittwer (BioTechniques)
Protocol Summary We have combined allele-specific PCR, competitive probe blocking, asymmetric PCR, and melting analysis to enhance rare allele detection in a homogeneous system. Unlabeled, dual hybridization or molecular beacon probes were used for competitive blocking of the wild-type allele at a concentration 10 times that of the allele-specific primer. In each case, rare alleles were detected by probe melting analysis at a sensitivity of >0.001% (1 variant copy within 100,000 wild-type copies), providing single copy detection in typical PCRs. Ninety-one thyroid biopsies were tested for the BRAF mutation p.V600E (c.1799 T > A) by both dual hybridization probes without enrichment and an allele-specific, competitive blocking melting analysis with unlabeled probes. Eighty-seven samples were concordant between methods (43 positive, 44 negative), while 4 samples that were negative by direct analysis became positive after enrichment. Probes that both block wild-type amplification and detect rare variants by melting analysis improve the detection sensitivity of allele-specific PCR for rare alleles. In particular, melting analysis using unlabeled probes and amplification by rapid-cycle PCR provides cost-effective and fast enrichment and detection of rare alleles.